Kantorovich Variant of Jain-Pethe Operators. (4th June 2021) - Gupta, Vijay; Bustamante, J.
Abstract: In the present paper we establish a link between the Jain-Pethe operators and its Kantorovich type integral modification, by applying the methods of finite differences. We also consider a modification of the Kantorovich variant, preserving affine functions and establish some direct results in weighted spaces.